Ratcheting in Renewable Resources Contracting - Urs Steiner Brandt; Frank Jensen; Lars Gårn Hansen; Niels Vestergaard (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2004)
Real life implies that public procurement contracting of renewable resources results in repeated interaction between a principal and the agents. The present paper analyses ratchet effects in contracting of renewable resources and how the presence of a resource constraint alters the standard ratchet effect result. We use a linear reward scheme to influence the incentives of the agents. It is shown that for some renewable resources we might end up both with more or with less pooling in the first-period compared to a situation without a resource constraint. The reason is that the resource constraint implies a smaller performance de-pendent bonus, which reduces the first-period cost from concealing information but at the same time the resource constraint may also imply that second-period benefits from this concealment for the efficient agent are reduced. In situations with high likelihood of first-period pooling, the appropriateness of applying lin-ear incentive schemes can be questioned.
Keywords: Q28; H2; H4; 330; Political support function; political economy; environmental regula-tion; lobbyism; rent-seeking; taxation; auction; grandfathering; emission trad-ing; European Union; interest groups; industry; consumers; environmentalists; Umweltabkommen; Joint Implementation; Klimaschutz; Internationale Umweltpolitik; Unvollkommene Information; Einkommenshypothese; Theorie